आधुुनिक भारतमा जाति र अन्य निबन्ध - Srinivas, M.N. (My University, 2020)
Through this book, the author has emphasized on 'empirical studies' and 'intensive field studies' to understand the elements of Indian social life such as varna, family, caste, caste-system, etc. so that an assessment of new meanings of caste and scientific outlook can be presented in the future of rural life.
Nepali translation of Caste in Modern India and Other Essays
Keywords: Nepali